Ambulatory blood pressure monitoring and morning surge in blood pressure in adult black and white South Africans. Issue 1 (25th November 2019) - Lambert, Gavin W.; Head, Geoffrey A.; Chen, Won Sun; Hamer, Mark; Malan, Nicolaas T.; Quinn, Stephen; Schlaich, Markus P.; Malan, Leone
Abstract: We examined whether there were differences in the circadian variation in blood pressure and the morning surge in blood pressure between black and white Africans. Clinic and ambulatory blood pressure data obtained from the Sympathetic Activity and Ambulatory Blood Pressure in Africans (SABPA) study was examined (n = 406; 49% black African). Ambulatory blood pressure readings were fitted to a six‐parameter double logistic equation to determine the power and rate of the morning surge in blood pressure. Multiple linear regression analysis was used to examine differences in blood pressure between black and white participants. Clinic and ambulatory blood pressure were higher in black participants throughout the day and night. In those taking medications, blood pressure was less well controlled in black subjects. Despite the higher systolic blood pressure, the day‐night difference estimated by the logistic function was similar in black and white participants. However, the rate of rise and power in the morning surge in blood pressure was lower in black participants. We conclude that black participants of the SABPA study present with higher blood pressure throughout the day and night but have a lower power of the morning surge in blood pressure due to a slower morning rate of increase. Moreover, they had an increased prevalence of undiagnosed hypertension and, in those taking medication, were less likely to have their blood pressure controlled than their white counterparts.